Upaya Mengatasi Bullying di Sekolah Dasar dengan Mensinergikan Program Sekolah dan Parenting Program melalui Whole-School Approach - Fery Muhamad Firdaus (Program Studi PGSD, Fakultas Ilmu Pendidikan, Universitas Negeri Yogyakarta, 2019)
Bullying is one of the phenomena that often arises in the world of education, including education in elementary schools, where this behavior is aggressive behavior that hurts others, both physically and psychologically. This bulliying problem needs to be addressed by schools through school programs that synergize with parenting programs through the whole-school approach. Therefore, there is a need for cooperation between schools, teachers and parents in overcoming this bulliying problem. The efforts that can be done by schools in synergizing school programs with parenting programs through the whole-school approach are as follows: (1) Activating the school committee which is a representative of the students' parents to design and implement collaboratively about the agreed school programs together, so regular meetings must be held. (2) Conducting a model teacher activity, where the teacher's representative simulates the learning process that is normally carried out so that parents can adjust teaching at home with at school. (3) Carry out activities between the school parties, students and parents of students so that there is a good relationship between various parties such as tourism activities, outbound and others.